EFQM management model and improvement of the quality of the educational service of the private educational institution San Antonio, Lima- 2020 - Rossell Carrasco, Rosa Elizabeth (2024)
The issue of quality has been recurring in recent times and there are strategies and models to achieve the long-awaited quality that affects the achievement of learning by the students of the San Antonio Private School in Lima. Therefore, the objective of this study is to determine the relationship that exists between EFQM (European Foundation for Quality Management) Management models and improve the quality of educational services at the San Antonio Private Educational Institution in Lima. We use scientific research with quantitative approaches, hypothetical deductive methods, cross sections and ordinal levels. The sample was made up of 7 managers, 148 students, 70 teachers, 16 administrative staff and 144 PPFF of the aforementioned institution, the sample size is determined with the formula and the sampling is probabilistic. Two tools were used: a questionnaire for measuring the variables of EFQM management models composed of 38 items, the measurement dimension: leadership, strategies, person, alliance and resource, as well as a process for measuring changes in the quality of the educational service. . , are validated in expert evaluations. and with sufficient reliability: EFQM Management Model with 0.836 and Quality of educational service with 0.812, measured using Cronbach's Alpha.  The result shows that the EFQM Management Model intervenes in significantly improving the quality of the educational services of the EI in question, since it has a p value, a significance less than 0.05, so the null hypothesis is rejected and the hypothesis is accepted. proposal. alternating and a high contribution coefficient r= .876